Anti‐HI can cause a severe delayed hemolytic transfusion reaction with hyperhemolysis in sickle cell disease patients. Issue 7 (3rd May 2016) - Ibanez, Clara; Habibi, Anoosha; Mekontso‐Dessap, Armand; Chadebech, Philippe; Chami, Btissam; Bierling, Philippe; Galactéros, Frédéric; Rieux, Claire; Nataf, Joëlle; Bartolucci, Pablo; Peyrard, Thierry; Pirenne, France
Abstract : BACKGROUND: Delayed hemolytic transfusion reaction (DHTR) is a life‐threatening condition in sickle cell disease (SCD) patients that is frequently complicated by hyperhemolysis. Antibodies resulting from antigen disparity between donors of European ancestry and patients of African ancestry are common, but situations involving antibodies not classically of clinical significance are also encountered. Anti‐HI is generally considered to be an innocuous naturally occurring antibody. STUDY DESIGN AND METHODS: We describe two cases of hyperhemolysis with anti‐HI and provide details of the reported cases. RESULTS: Both SCD patients were polyimmunized and belonged to blood group B. They developed anti‐HI that was reactive at 37°C, after the transfusion of group O red blood cell units matched for all known and produced antibodies classically considered to be clinically significant. Both patients developed DHTR with hyperhemolysis. In the first case, a pregnant woman, a second transfusion was unavoidable and the patient died from cardiac arrest. The state of the second patient improved without the need for further transfusion. CONCLUSION: Three other cases of DHTR with anti‐HI have been described in the literature in SCD patients. The two additional cases reported here definitively demonstrate that anti‐HI is dangerous in SCD patients. As a result, ABO‐identical matching (including A1 status) must be considered in SCD patients with anti‐HI.